2008
DOI: 10.1200/jco.2008.16.9524
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study Comparing Docetaxel, Estramustine, and Prednisone With Docetaxel and Prednisone in Metastatic Hormone-Refractory Prostate Cancer

Abstract: The addition of estramustine to weekly D does not provide any clinically relevant advantage. Both regimens are well tolerated, although the toxicity profile favors D without estramustine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…However, a recent randomized trial comparing docetaxel, estramustine and prednisone with docetaxel and prednisone [24] has shown that the combination of docetaxel and estramustine has no apparent effect either on PSA response rate (73% versus 69%) or on survival (median 19.3 versus 21 months), with a poorer toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent randomized trial comparing docetaxel, estramustine and prednisone with docetaxel and prednisone [24] has shown that the combination of docetaxel and estramustine has no apparent effect either on PSA response rate (73% versus 69%) or on survival (median 19.3 versus 21 months), with a poorer toxicity profile.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy has only limited efficacy in AIPC and HRPC (12). During androgen-dependent progression, prostate cancer cells depend on the androgen receptor as the primary mediator of growth and survival.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…7 Furthermore, the addition of estramustine to docetaxel and prednisone did not provide any clinical advantage and more digestive and cardiovascular toxicities were reported. 8 According to these data, docetaxel plus prednisone is considered the gold standard first-line chemotherapy for CRPC. Unfortunately, median OS for patients affected by metastatic prostate cancer is less than 20 months.…”
Section: Medical Strategies For Treatment Of Castration Resistant Promentioning
confidence: 99%